Evaluation of The User Experience of A Healthtech Application And Its Impact on Patient Satisfaction - Moh Khoirul Anam (Public Health and Safety International Journal, 2025)
The digital transformation in healthcare services has increased the role of HealthTech applications in enhancing efficiency and patient satisfaction. However, adoption remains challenging due to suboptimal user experience. This study examines the user experience of HealthTech applications and its impact on patient satisfaction at Ayu Siwi Eye Clinic, Nganjuk. This quantitative research adopts a case study design, collecting primary data through questionnaires from 30 employees and 30 patients, while secondary data were sourced from patient satisfaction forms and relevant documents. Simple random sampling was applied, and data were analyzed using SPSS, including descriptive analysis, validity and reliability tests, simple regression, and classical assumption tests. Findings reveal a significant relationship (p = 0.034) between user experience and patient satisfaction, where better user experience characterized by ease of use, usability, and effectiveness correlates with higher satisfaction. The R-squared value (0.151) indicates that user experience explains 15.1% of patient satisfaction variance, with other factors influencing the rest. To improve satisfaction, Ayu Siwi Eye Clinic should refine application design and provide regular staff training. This study underscores the importance of user experience in HealthTech adoption, recommending future research to increase the sample size and explore additional variables like digital literacy and social media influence.